Effect of Metformin in HbA1C in Nepalese Type 2 Diabetes - Tiwari, Sanjeeb (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Up to now a limited number of studies compared metformin with other OHA directly and some of their results are still controversial.1 The study which compared metformin and other OHA, the ADOPT study, the U.K. Prospective Diabetes Study (UKPDS), did not include Nepalese diabetic patients . Therefore, the aim of study was the comparative evaluation of metformin and other OHA influence on glycemic control(HbA1c) in Nepalese patients with diagnosed type 2.Methods: A prospective cross sectional database of patients treated at diabetic clinic, TUTH, were analyzed. Patients with type 2 diabetes with HbA1c (A1C) data and treated with metformin and other OHA, for at least three visits were included (n = 115). Analysis by HbA1c and the type of oral agent was performed.Results: In the analyzed group of patients, the mean duration of therapy was for 9 months. Metformin was given to 48 patients and 57 patients were on other OHA. In the metformin group mean HbA1c level (from 7.8 ± 1.8 at baseline to 6.7 ± 0.8 at the end of analysis period; p